Boltzmann-Enskog limit for equilibrium states of systems of hard spheres in the framework of a canonical ensemble - Lampis, M.; Petrina, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove the existence of the Boltzmann-Enskog limit for an equilibrium system of hard spheres. On the basis of analysis of the Kirkwood-Salsburg equations, we show that the limit distribution functions are constants that can be represented as series in density.